Epstein-Barr virus, cytomegalovirus, and multiple sclerosis susceptibility: A multiethnic study. (26th September 2017) - Langer-Gould, Annette; Wu, Jun; Lucas, Robyn; Smith, Jessica; Gonzales, Edlin; Amezcua, Lilyana; Haraszti, Samantha; Chen, Lie Hong; Quach, Hong; James, Judith A.; Barcellos, Lisa F.; Xiang, Anny H.
Abstract : Objective: To determine whether Epstein-Barr virus (EBV) or cytomegalovirus (CMV) seropositivity is associated with multiple sclerosis (MS) in blacks and Hispanics and to what extent measures of the hygiene hypothesis or breastfeeding could explain these findings. EBV and CMV have been associated with MS risk in whites, and the timing and frequency of both viruses vary by factors implicated in the hygiene hypothesis. Methods: Incident cases of MS or its precursor, clinically isolated syndrome (CIS), and matched controls (blacks, 111 cases/128 controls; Hispanics, 173/187; whites, 235/256) were recruited from the membership of Kaiser Permanente Southern California. Logistic regression models accounted for HLA-DRB1*1501 status, smoking, socioeconomic status, age, sex, genetic ancestry, and country of birth. Results: Epstein-Barr nuclear antigen-1 (EBNA-1) seropositivity was independently associated with an increased odds of MS/CIS in all 3 racial/ethnic groups ( p < 0.001 for blacks and whites, p = 0.02 for Hispanics). In contrast, CMV seropositivity was associated with a lower risk of MS/CIS in Hispanics ( p = 0.004) but not in blacks ( p = 0.95) or whites ( p = 0.96). Being born in a low/middle-income country was associated with a lower risk of MS in Hispanics ( p = 0.02) but not after accounting for EBNA-1 seropositivity. Accounting for breastfeeding did not diminish the association between CMV and MS in Hispanics. Conclusions: The consistency of EBNA-1 seropositivity with MS across racial/ethnic groups and between studies points to a strong biological link between EBV infection and MS risk. The association between past CMV infection and MS risk supports the broader hygiene hypothesis, but the inconsistency of this association across racial/ethnic groups implies noncausal associations.